Ayahuasca and the process of regulation in Brazil and internationally: Implications and challenges - Labate, Beatriz Caiuby; Feeney, Kevin (International journal of drug policy, 2012)
Background: This paper provides a summary and analysis of the regulation of ayahuasca in Brazil, from its prohibition in the mid-eighties to the recent adoption of CONAD's (Conselho Nacional de Políticas sobre Drogas) 2010 Resolution, which established a set of rules, norms and ethical principles to be applied to religious and ritual uses of ayahuasca. Brazil's regulatory process is used as a starting point to explore emerging international regulatory themes as various nations respond to the global expansion of the Santo Daime and UDV (União do Vegetal) ayahuasca religions. Methods: The text reviews the primary legislative and court documents, academic literature, as well as solicited expert opinions. Results: Three prominent themes have emerged internationally. The first concerns the scope of international treaties regarding plant-based psychoactive substances, as well as the responsibilities of individual nations to adhere to said treaties. The second concerns the scope of religious liberty and how to determine religious legitimacy. The final theme addresses the potential dangers of ayahuasca to health and public safety. Conclusion: Over the past 20 years the Brazilian ayahuasca religions have established a global presence, with congregations in the USA, Canada, Japan, South Africa, Australia, and throughout Europe and Latin America. As a result, many nations are faced with the predicament of balancing the interests of these religious minorities with the international “war on drugs.” The regulatory process applied in Brazil exemplifies a progressive approach, one which considered issues of anthropology and involved representatives of ayahuasca religions, and which provided a degree of deference to the principle of religious liberty. The Brazilian process has influenced judicial and administrative decisions internationally, and stands as a model worthy of further consideration.
Available online 18 August 2011
Gesehen am 30.10.2018